Synergy between Islamic Philanthropy and the Government: Optimizing Zakat-Wakf Based on Maslahah Daruriyyah and Fiqh al-awlawiyyat in Alleviating Social Problems - Fitriah Raudhatul Jannah; Dedy Purnomo; Jamilah Zahra; Mudawamatul Ummah; Rina Alifiyah; Chika Arta Dhuana Pangestu; Muhammad Ikhsanudin; Amelia Putri; Muhammad As'ad Samsul Arifin; Hurin 'In Lu'Lu'il Maknun; Asyifa Raudhatul Jannah; Haikal Akbar Karim (West Science Journal Economic and Entrepreneurship, 2026)
Indonesia has enormous potential for zakat and waqf as instruments of Islamic philanthropy, but their utilization has not been optimal in addressing fundamental social issues. Zakat management still tends to be consumer-oriented, while waqf is more directed at the construction of places of worship, so that their function as instruments of sustainable social protection has not been optimally achieved. This study aims to analyze the synergy model between the National Zakat Agency (BAZNAS), the Indonesian Waqf Agency (BWI), and the Social Service in managing zakat and waqf based on maslahah daruriyyah and fiqh al-awlawiyyat. This study uses a qualitative method with a juridical-normative approach through a literature review of relevant fiqh literature, regulations, and institutional data. The results show that the low social impact of zakat and waqf is caused by inaccurate allocation priorities, weak institutional integration, and a lack of orientation towards meeting the basic needs of vulnerable groups. This study concludes that institutional synergy is needed to direct zakat as a supporter of short-term social financing and waqf as a provider of sustainable social infrastructure, so that Islamic philanthropy can play an effective role in strengthening social welfare.